Rainbow Connection Number on Amalgamation of General Prism Graph - Rizki Hafri Yandera; Yanne Irene; Wisnu Aribowo (Department of Mathematics, Faculty of Sciences and Technology, UIN Syarif Hidayatullah, 2019)
AbstractLet be a nontrivial connected graph, the rainbow-k-coloring of graph G is the mapping of c: E(G)-> 1,2,3,…,k such that any two vertices from the graph can be connected by a rainbow path (the path with all edges of different colors). The least natural number